Gender aspects in cardiooncology. (13th September 2021) - Hohneck, Anna; Custodis, Florian; Rosenkaimer, Stephanie; Hofheinz, Ralf; Maier, Sandra; Akin, Ibrahim; Borggrefe, Martin; Gerhards, Stefan
Abstract: Background: Cardiooncology is a relatively new subspeciality, investigating the side effects of cytoreductive therapies on the cardiovascular (CV) system. Gender differences are well known in oncological and CV diseases, but are less elucidated in cardiooncological collectives. Methods: Five hundred and fifty-one patients (278 male, 273 female) with diagnosed cancer who underwent regular cardiological surveillance were enrolled in the 'MA nnheim R egistry for C ardioO ncology' and followed over a median of 41 (95% confidence interval: 40–43) months. Results: Female patients were younger at the time of first cancer diagnosis [median 60 (range 50–70) vs. 66 (55–75), P = 0.0004], while the most common tumour was breast cancer (49.8%). Hyperlipidaemia was more often present in female patients (37% vs. 25%, P = 0.001). Male patients had a higher cancer susceptibility than female patients. They suffered more often from hypertension (51% vs. 67%, P = 0.0002) or diabetes (14% vs. 21%, P = 0.02) and revealed more often vitamin D deficiency [(U/l) median 26.0 (range 17–38) vs. 16 (9–25), P = 0.002] and anaemia [(g/dl) median 11.8 (range 10.4–12.9) vs. 11.7 (9.6–13.6), P = 0.51]. During follow-up, 140 patients died (male 77, female 63; P = 0.21). An increased mortality rate was observed in male patients (11.4% vs. 14%, P = 0.89), with even higher mortality rates of up to 18.9% vs. 7.7% ( P = 0.02) considering tumours that can affect both sexes compared. Conclusions: Although female patients were younger at the time of first cancer diagnosis, male patients had both higher cancer susceptibility and an increased mortality risk. Concomitant CV diseases were more common in male patients.